The Effect of Muscular Strength on Depression Symptoms in Adults: A Systematic Review and Meta-Analysis - De Moraes-Ferrari, G (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
The aim was to systematically review the relationship between muscular strength (MS) and depression symptoms (DS) among adults, and conduct a meta-analysis to determine the pooled odds ratio (OR) for the relationship between MS and DS. The strategies employed in this systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Studies published up to December 2019 were systematically identified by searching in the PubMed, Scopus, and Web of Science electronic databases. Inclusion criteria were: (1) cross-sectional, longitudinal and intervention studies; (2) outcomes included depression or DS; (3) participants were adults and older adults; and (4) the articles were published in English, French, Portuguese, or Spanish. A total of 21 studies were included in the review, totalling 87,508 adults aged ≥18 years, from 26 countries. The systematic review findings suggest that MS has a positive effect on reducing DS. Meta-analysis findings indicate that MS is inversely and significantly related to DS 0.85 (95% CI: 0.80, 0.89). Interventions aiming to improve MS have the potential to promote mental health and prevent depression. Thus, public health professionals could use MS assessment and improvement as a strategy to promote mental health and prevent depression. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.